Judging Lincoln - Williams, Frank J. (Book collections on Project MUSE., 2002)
Judging Lincoln collects nine of the most insightful essays on the topic of the sixteenth president written by Frank J. Williams, chief justice of the Rhode Island Supreme Court and one of the nation's leading authorities on Abraham Lincoln.